Comparing 'Twitter' polls results with an online survey on surgeons perspectives for the treatment of rectal cancer. Issue 1 (28th September 2020) - Caycedo-Marulanda, Antonio; Patel, Sunil V; Verschoor, Chris P; Chadi, Sami A; Möslein, Gabriela; Raval, Manoj; Lightner, Amy; Chand, Manish; Jimenez-Rodriguez, Rosa; Knol, Joep; Maeda, Yasuko; Monson, John R T; et al.
Abstract : Introduction: Traditional surveys (including phone, mail and online) can be valuable tools to obtain information from specific communities. Social media apps such as Twitter are being increasingly adopted for knowledge dissemination and research purposes. Twitter polls are a unique feature which allows for a rapid response to questions posed. Nonetheless Twitter does not constitute a validated survey technique. The objective was to compare the similarities of Twitter polls in describing practice patterns for the treatment of rectal cancer. Methods: A survey on the management of rectal cancer was designed using modified Delphi methodology. Surgeons were contacted through major colorectal societies to participate in an online survey. The same set of questions were periodically posted by influencers on Twitter polls and the results were compared. Results: A total of 753 surgeons participated in the online survey. Individual participation in Twitter ranged from 162 to 463 responses. There was good and moderate agreement between the two methods for the most popular choice (9/10) and the least popular choice (5/10), respectively. Discussion: It is possible that in the future polls available via social media can provide a low-cost alternative and an efficient, yet pragmatic method to describe clinical practice patterns. This is the first study comparing Twitter polls with a traditional survey method in medical research. Conclusions: There is viable opportunity to enhance the performance of research through social media, however, significant refinement is required. These results can potentially be transferable to other areas of medicine.